Efeito antidepressivo, ansiolítico e neuroprotetor do alfa-Bisabolol em modelos in vivo e in vitro de indução por lipopolissacarídeo - Rebouças, Manoela de Oliveira (2024)
Seeking treatment for neuropsychiatric disorders, such as depression, is of great relevance to public health, given their disabling nature. In a scenario where the increasing involvement of neuroinflammation and diseases that affect the Central Nervous System (CNS) is perceived, interest is aroused in evaluating research with anti-inflammatory potential as a therapeutic alternative with a specifically neuroprotective effect. In this context, compounds such as terpenoids are strong candidates for this purpose, such as α-bisabolol (BIS), a sesquiterpene alcohol with many biological activities, including anti-inflammatory properties. Therefore, the objective of the present work was to verify the neuroprotective potential of BIS in an in vivo and in vitro inflammation model after exposure to lipopolysaccharide (LPS) from Escherichia coli. For this, male mice of the C57BL/6 lineage were subjected to a model of systemic administration of LPS (0.5mg/kg) for ten days and treated from the 5th day onwards with BIS (50mg/kg), saline (0. 9%), escitalopram (10mg/kg) or dexamethasone (2mg/kg). On the last day, the animals performed behavioral tests to evaluate the depressive and anxiety-like profile, in addition to performing a short-term memory test. In addition, levels of reactive oxygen species (ROS), nitrogen, and pro-inflammatory cytokines were measured in the hippocampus and prefrontal cortex. In the in vitro model, the effect of BIS on cellular options in PC12 lines and astrocytes is provided through the MTT test and propidium iodide labeling. ROS, mitochondrial transmembrane potential, pro-inflammatory cytokines IL-1β, IL-6, and INFγ, and the pattern of cell death of the two lines exposed to LPS and treated with BIS were measured. Finally, the cells were evaluated for morphology using the Scanning Electron Microscope (SEM). To search for molecular targets, molecular docking was performed to verify the BIS binding layer with TLR4, HMOX, and PI3K targets. The results demonstrated that BIS did not present a psychostimulant and relaxing effect, evidenced in the open field test, and also prevented the frequency of stereotypical behavior (creation) indicative of anxiety-like. Furthermore, treatment with BIS reversed similar depressive behavior in animals, evidenced by the forced swim test and Splash, in addition to improving the symptom of anhedonia in the sucrose solution preference test. Furthermore, we tested ourselves to evaluate the anxiolytic profile of BIS, reversing the behavior caused by LPS and improving short-term memory impairment. BIS provided reduced substances reactive to thiobarbituric acid and nitrite and altered cytokine levels. As for the in vitro model, in cellular predictions, there was an improvement in treatment with BIS and a reduction in the occurrence of apoptotic and necrotic events in both cell lines. ROS production was reduced about BIS, and mitochondrial transmembrane potential was maintained.Furthermore, the levels of pro-inflammatory cytokines were reverted to levels comparable to the control, demonstrating a potential neuroprotective effect of α-bisabolol in the LPS exposure model. Molecular docking demonstrated the binding stability of BIS with the targets TLR4, HMOX, and PI3K, with HMOX being the target with the most incredible depth and focusing on exploring new therapeutic targets. Given the reduced damage observed, α-bisabolol proved favorable for neuroinflammatory diseases like depression.